Contraindications of COVID-19 Vaccines: A Letter to Editor - Javad Ghaffari (Mazandaran University of Medical Sciences, 2023)
Coronavirus disease 2019 (COVID‐19, the 7th coronavirus) was a pandemic infectious disease with significant morbidity and mortality in the world. The respiratory system is often involved in COVID-19 infection. Underlying disorders such as uncontrolled asthma are a risk factor for COVID-19 infection. For protecting against COVID-19, we need vaccination-associated social care such as facial masks, distance, and sanitizers.